Implementing EDI solutions - Putte, Geert van de (IBM redbooks., 2003)
This IBM Redbooks publication introduces the reader to the world of EDI. In addition to general terms about EDI, it also introduces a number of products in this area. WebSphere Data Interchange is discussed as the translation engine to map EDI documents to and from documents in other formats. This book also introduces two communication products that use Internet technologies: iSoft's P2PAgent and Trading Partner Interchange. In addition to product introductions, the book describes several implementation scenarios in a multi-partner and multi-product environment. Besides a network where trading partners only use iSoft's P2PAgent, we also look at a setup where trading partners use a combination of the two products. For each communication product, we investigate several integration options with internal applications and other middleware. We discuss the integration options with the translation product WebSphere Data Interchange and with the process integration product WebSphere BI Interchange Server. The integration technique can be file-based or messaging-based. Finally, we take a look at options to combine the flexibility of the Internet with the reliability of value-added networks. When Internet connectivity is temporarily not available, a trading partner has the ability to use Expedite to dial into IBM's network and send or receive EDI documents. By exploiting the recycle mechanics in iSoft's P2PAgent, we can implement a solution that provides a highly available connection between trading partners. For more up-to-date information about WebSphere B2B, please refer to the following books: B2B solutions using WebSphere Partner Gateway V6.0, http://www.redbooks.ibm.com/abstracts/sg247109.html?Open and Secure Production Deployment of WebSphere Business Integration Connect, http://www.redbooks.ibm.com/abstracts/sg246457.html?Open. Please note that the additional material referenced in the text is not available from IBM.